Contemporary Logistics in China Transformation and Revitalization - Liu, Bing-lian.; Lee, Shao-ju.; Xiao, Jian-hua.; Wang, Ling.; Jiao, Zhi-lun. (Current Chinese Economic Report Series,, 2013)
Driven by decades of steady economic growth in China, logistics has now taken center stage in the nations development plan, and both infrastructural construction and operations systems have been improved to propel logistics into a new era. This book, the second volume of the series on Contemporary Logistics in China, is a just-in-time publication which introduces readers to the logistics development in China for this pivotal period. The papers are founded on the up-to-date studies of a team of dedicated researchers, and supported by the reputable Logistics Research Center at Nankai University. The book presents a comprehensive and thorough analysis of the progression and transformation of modern-day logistics in China, as well as the critical issues and perspectives involved in it. Researchers and practicing professionals alike will find this book an indispensable and just-in-time reference and information resource.